Climate and the oceans - Vallis, Geoffrey K. (Princeton, N.J. : Princeton University Press, 2012)
Explores climate and oceans, providing a look at the basics of climate, a descriptive overview of the oceans, a brief introduction to dynamics, and coverage of other related topics.
Includes bibliographical references (p. [211]-213) and index.
Keywords: Ocean-atmosphere interaction -- Popular works; Climatic changes -- Popular works; Ocean -- Popular works; Oceanography -- Research -- Popular works